2010
DOI: 10.1051/dst/2010032
|View full text |Cite
|
Sign up to set email alerts
|

Dairy propionibacteria as human probiotics: A review of recent evidence

Abstract: Probiotics have been the subject of intensive research, mainly focusing on bifidobacteria and lactic acid bacteria. However, there is evidence that dairy propionibacteria also display probiotic properties, which as yet have been underestimated. The aim of this paper is to review recent data which report probiotic characteristics of dairy propionibacteria and to distinctly organise them based on the experimental strategy employed: ranked from in vitro evidence to in vivo trials, which is a new approach. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
77
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 136 publications
(250 reference statements)
0
77
0
4
Order By: Relevance
“…At present, no cases of sickness or toxicity after the ingestion of dairy propionibacteria have been reported [122] neither for humans (for a review of human trials see [123]) nor for animals [124][125][126]. In fact, it has been reported that propionibacteria did not translocate to blood, liver or spleen and no adverse effects on body weight gain and general health status was observed after short [124,127] and long terms [125] administration of strains of Propionibacterium acidipropionici, P. freudenreichii and P. jensenii, respectively.…”
Section: Safety and Persistence In The Gutmentioning
confidence: 99%
“…At present, no cases of sickness or toxicity after the ingestion of dairy propionibacteria have been reported [122] neither for humans (for a review of human trials see [123]) nor for animals [124][125][126]. In fact, it has been reported that propionibacteria did not translocate to blood, liver or spleen and no adverse effects on body weight gain and general health status was observed after short [124,127] and long terms [125] administration of strains of Propionibacterium acidipropionici, P. freudenreichii and P. jensenii, respectively.…”
Section: Safety and Persistence In The Gutmentioning
confidence: 99%
“…Consumption of fermented products has an impact on immune system function (25), and the bacterial content of these products is responsible for immunomodulation (6,10). Dairy propionibacteria display various probiotic properties either similar to or distinct from those reported for probiotic bifidobacteria and lactic acid bacteria (3). Although an anti-inflammatory potential of a few dairy propionibacterium strains was occasionally suggested in vitro (15) or in animals (22,24,31), no reliable observation was established in terms of strain variability and of specific mechanisms involved.…”
mentioning
confidence: 99%
“…пропионовая кислота, образованная в цикле ВудаВеркмана, транспор тируется в печень и включается в процесс глюконеогенеза и синтеза биогенных аминов, улучшает микроциркуляцию в слизистой кишечника и поддерживает в ней метаболические процессы, блокирует прикрепление к колоноцитам условнопатогенной микробиты, и в тоже время стимулирует рост анаэробных бактерий нормальной микробиоты ЖКТ [11,17,18]. [6][7][8][9][10][11][12][13][14][15] Витамин В 12 является необычным в отношении своего происхождения. Практически все витамины могут быть выделены из разнообразных растений или животных но, ни одно растение или животное не способно производить витамин B 12 .…”
unclassified
“…На образование витамина благоприятное влияние оказывает наличие молочной кислоты, создавая элективностъ условий [5,11,18].…”
unclassified
See 1 more Smart Citation